Industrial Policy of Germany: Highlights and the Most Important Areas - K. N. Andrianov (Vestnik MGIMO-Universiteta)
This article examines in detail the basis of industrial policy in Germany. The analysis of goals, actors and tools of the German industrial policy. Special attention is given to the regional dimension of industrial policy in Germany, in particular, looks at the experience of regional industrial policy in Bavaria. In addition, this article describes the types of industrial policy in Germany: the horizontal and sectoral